Population dynamics of Sardinella aurita (Val., 1847) within Ghana’s coastal waters - Amponsah, Samuel KK; Danson, Patrick K Ofori; Nunoo, Francis KE; Ameyaw, Godfred A (Research in Agriculture Livestock and Fisheries, 2017)
Following the declining stocks of Sardinella aurita within the coastal waters of Ghana, this study aimed at examining some population parameters of Sardinella aurita as a guide for managing this important stock sustainably. Length-frequency data of 717 samples were obtained from June, 2014 to January 2015 and measured for total length with the resultant data analyzed using FiSAT II. The asymptotic length (L∞) and growth rate (K) were 21.53 cm SL and 0.25yr-1 respectively. The theoretical age at birth (t0), longevity (tmax) and growth performance index (ϕ) were -0.74yr-1, 12 years and 1.849 respectively. Total mortality rate (Z), natural mortality rate (M) and fishing mortality rate (F) were 3.17, 0.76 and 2.41yr-1 respectively. The ages at first recruitment and first capture signaled future collapse of the stock, in the absence of proper management interventions. VPA outcome showed that mid- lengths of 11 cm and 12 cm SL experienced the highest harvesting rate with MSY estimated at 7733 tons. The recruitment pattern was continuous with two major recruitment pulses. Exploitation rate (Ecurr=0.76) was higher than the maximum exploitation rate (Emax=0.56), indicating unsustainable exploitation. Further, the fishing regime fell within the overfished stage based on the Quadrant Rule. For sustainable exploitation of this commercial fish species, implementation of relevant biological reference points through reduction in fishing efforts, creation of marine protected areas and mesh size regulation are urgently advocated. Res. Agric. Livest. Fish.4(3): 237-248, December 2017